Breakdown in the temporal and spatial organization of spontaneous brain activity during general anesthesia. Issue 5 (28th January 2018) - Zhang, Jianfeng; Huang, Zirui; Chen, Yali; Zhang, Jun; Ghinda, Diana; Nikolova, Yuliya; Wu, Jinsong; Xu, Jianghui; Bai, Wenjie; Mao, Ying; Yang, Zhong; Duncan, Niall; et al.
Abstract: Which temporal features that can characterize different brain states (i.e., consciousness or unconsciousness) is a fundamental question in the neuroscience of consciousness. Using resting‐state functional magnetic resonance imaging (rs‐fMRI), we investigated the spatial patterns of two temporal features: the long‐range temporal correlations (LRTCs), measured by power‐law exponent (PLE), and temporal variability, measured by standard deviation ( SD ) during wakefulness and anesthetic‐induced unconsciousness. We found that both PLE and SD showed global reductions across the whole brain during anesthetic state comparing to wakefulness. Importantly, the relationship between PLE and SD was altered in anesthetic state, in terms of a spatial "decoupling." This decoupling was mainly driven by a spatial pattern alteration of the PLE, rather than the SD, in the anesthetic state. Our results suggest differential physiological grounds of PLE and SD and highlight the functional importance of the topographical organization of LRTCs in maintaining an optimal spatiotemporal configuration of the neural dynamics during normal level of consciousness. The central role of the spatial distribution of LRTCs, reflecting temporo‐spatial nestedness, may support the recently introduced temporo‐spatial theory of consciousness (TTC).